2017
DOI: 10.14316/pmp.2017.28.4.197
|View full text |Cite
|
Sign up to set email alerts
|

Proposal on Guideline for Quality Assurance of Radiation Treatment Planning System

Abstract: We develop guidelines for the quality assurance of radiation treatment planning systems (TPS) by comparing and reviewing recommendations from major countries and organizations, as well as by analyzing the AAPM, ESTRO, and IAEA TPS quality assurance guidelines. We establish quality assurance items for acceptance testing, commissioning, periodic testing, system management, and security, and propose methods to perform each item within acceptable standards. Acceptance includes tests of hardware and network environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…These results are in line with previously reported studies. Oh et al (2017) reviewed and suggested the QA of planning systems that can also be used for the commissioning. The end-to-end tests are per these recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previously reported studies. Oh et al (2017) reviewed and suggested the QA of planning systems that can also be used for the commissioning. The end-to-end tests are per these recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…9) The modeling and dose verification process were previously reported for the commissioning of the radiation treatment plan (RTP) system. 11) In this paper, we derive procedures focusing on the acquisition of beam data in high precision external radiation therapy equipment. Dosimetry systems used in the ATP and commissioning phases include ionization chambers, electrometers for one-dimensional dose measurement, radiochromic films, and two-dimensional array detectors for two-dimensional dose distribution measurements.…”
Section: Methodsmentioning
confidence: 99%
“…• Muchos de los errores que se dan en radioterapia están relacionados con el uso inadecuado de los sistemas de planificación. [125][126][127][128] • La configuración de las unidades de tratamiento en el TPS afecta a todos los pacientes planificados con el mismo. Existen parámetros y ajustes clave dentro del estado de referencia inicial que determinan el cálculo para todos o gran parte de los planes que va a producir el sistema por lo que los errores en esta configuración son potencialmente graves.…”
Section: Análisis De Riesgos Asociados Al Sistema De Planificaciónunclassified